DNS blocking in AE: bbc.com, facebook.com, google.com, instagram.com, medium.com +13 more (United Arab Emirates) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in United Arab Emirates. Data sourced from CensoredPlanet.
Censorship Incident ID: AE-2026-0001. Severity: critical. Confidence: 85%